Early burst of parallel evolution describes the diversification of gecko toe pads - McCann, Jenny; Hagey, Travis J. (Frontiers in Ecology and Evolution, 2024)
Our study investigates how gecko lizards evolved the wide range of adhesive toe pad shapes seen today in living species. Using their phylogeny as a framework to investigate patterns of trait evolution, we found that different clades of geckos likely evolved along the same lines, changing in similar ways from ancestors without pads to distantly related groups of geckos with very Deleted: 7 46 Deleted: 3 47 2 similar adhesive toe pads. These parallel changes likely occurred quickly at first around 80 million years ago, and then slowed over time.